If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -144 = -12x + 116 Reorder the terms: -144 + x = -12x + 116 Reorder the terms: -144 + x = 116 + -12x Solving -144 + x = 116 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -144 + x + 12x = 116 + -12x + 12x Combine like terms: x + 12x = 13x -144 + 13x = 116 + -12x + 12x Combine like terms: -12x + 12x = 0 -144 + 13x = 116 + 0 -144 + 13x = 116 Add '144' to each side of the equation. -144 + 144 + 13x = 116 + 144 Combine like terms: -144 + 144 = 0 0 + 13x = 116 + 144 13x = 116 + 144 Combine like terms: 116 + 144 = 260 13x = 260 Divide each side by '13'. x = 20 Simplifying x = 20
| 1.65s=80 | | 22.5=7h+6h | | 4y(y+2)=7 | | 600/400 | | (x^(-3)y^4/x^3y^7)^2 | | 6x-1/18 | | 13j=169 | | -44+12x=4x+60 | | 6y-13-3y+9=0 | | 8x-111=-2x+149 | | 3x+5+25+x-10=180 | | -4c+2c+(-5)c=-1 | | G/48=11/12 | | 5x-5=25x-7 | | 6sin^2x+11sinx+5=0 | | 0.5(8c-12)-6=5x-14 | | 484=4+2a*72 | | 2.1x+3.2=-9.4 | | By-3by= | | (3.6+m)7=83.3 | | 6sin^2x-11sinx+5=0 | | 15(t+6m)+9t=6 | | e^2x+1=34 | | 4/3pi10^3 | | (6.3+m)7=83.3 | | 4x+6x-18=72-8x | | 11+a^3=17 | | -2m=4 | | 3z+5=2(z-8) | | 6(2+3x)=192 | | 3t=5-7t-2 | | 12y^2+20y=0 |